The Role Of Upper And Lower Body Strength Balance On Three-Point And Free-Throw Accuracy In Collegiate Basketball Players - Irawati, Andi Febi; Aziz, Muhammad Ivan Miftahul (Indonesian Journal of Physical Education and Sport Science, 2025)
Study purpose. This study aims to analyze the role of upper and lower body strength balance on three-point shooting accuracy and free throws in college basketball players. The balance of upper and lower body strength is one of the important factors in supporting the ability of shooting techniques, especially in static and dynamic situations. Materials and methods. The research method used was quantitative correlational involving 17 purposively selected college basketball athletes. The instruments used included an upper body strength test using Bench Press 1 Repetition Maximum, a lower body strength test using Back Squat 1 Repetition Maximum, and a three-point throw accuracy test and free throw. The data were analyzed using simple regression and correlation techniques. Result. The results showed that there was a significant relationship between the balance of upper and lower body strength (UB/LB ratio) and the accuracy of free throws (R² = 0.362; p = 0.011) and three-point throws (R² = 0.485; p = 0.002). The regression equation obtained for free throws is Free-Throw = 2.24 + 5.97 × UB/LB Ratio, while for three-point throws is Three-Point = -0.97 + 8.00 × UB/LB Ratio. Conclusion. These results show that the more balanced the upper and lower body strength, the higher the level of shot accuracy achieved, with a greater contribution to the influence on the three-point shot. This study recommends the importance of an exercise program that emphasizes the balance of upper and lower body strength as an effort to improve the shooting performance of basketball players.